2016
DOI: 10.1016/j.canep.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Trends in mouth cancer incidence in Mumbai, India (1995⿿2009): An age-period-cohort analysis

Abstract: HighlightsWe conducted an age-period-cohort (APC) analysis of mouth cancer in Mumbai, India.An overall upward trend was observed in 1995–2009 for men but not women.The increase was mainly in younger men (aged 25–49 years).A suggestive increase was also seen in younger women (aged 25–49 years).Our data suggest a need for focused tobacco control efforts in younger cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 21 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…According to NCRP data from Mumbai, the incidence of mouth cancer increased sharply in men from 1999 to 2009 (3.3% annually), while it increased somewhat in women from 2002 to 2009. [ 39 ] The world’s highest incidence rates of oral cancer have been found in South Asian nations like Bangladesh, India, Pakistan, Sri Lanka, and Taiwan. These countries’ chewing practices of tobacco and betel nut combined with a lack of knowledge and access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…According to NCRP data from Mumbai, the incidence of mouth cancer increased sharply in men from 1999 to 2009 (3.3% annually), while it increased somewhat in women from 2002 to 2009. [ 39 ] The world’s highest incidence rates of oral cancer have been found in South Asian nations like Bangladesh, India, Pakistan, Sri Lanka, and Taiwan. These countries’ chewing practices of tobacco and betel nut combined with a lack of knowledge and access to health care.…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] A report analyzing the Mumbai Cancer Registry found that the rates of oral cancer have been steadily rising over 15 years, from 1995 to 2009, at the rate of 2.7% annually. [ 14 ] A study from South India reported the overall incidence of HNSCC to have been decreasing over 10 years from 1986 to 98, however, a trend toward rising incidence of oral tongue cancers was noted. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Oral cancer is a malignant tumor that occurs in tissues and organs within the oral cavity and usually originates from cells in the oral cavity and can spread to lymph nodes in the neck, other tissues and organs in the head and neck, and even other parts of the body [ 1 , 2 ]. The age of onset of oral cancer is mainly in the range of 40–70 years, and incidence of oral cancer is higher in developed countries, as well as in parts of Asia and Africa [ 3 ]. Oral cancer can occur at various sites within the oral cavity, such as the lip, tongue, and oral mucosa, and has many types, is aggressive, is easy to recur, and early symptoms will be slight pain, discomfort, ulceration, and so on, which can be easily overlooked or misdiagnosed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%